Immobilisation of electric eel acetylcholinesterase on nanofibres electrospun from a nylon and chitosan blend - Mafuma, Tendai Simbarashe (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
Organophosphates and carbamates are potent inhibitors of the neurotransmitter acetylcholinesterase. This inhibition results in the blocking of nerve signal transference into the post synaptic neuron leading to loss of muscle action and death. Because of the universal mechanisms of signal transduction in animals, these inhibitors have been widely used as agricultural pesticides as well as chemical warfare agents (nerve agents). Health issues associated with pesticide usage result from the fact that both the pesticides and their breakdown products often end up in water and food sources as well as in the soil. As a result, there has been an increase in the number of studies aimed at the detection of these pesticides in the environment. One popular research area is enzyme based biosensor construction. Some important criteria for consideration during the construction of biosensors are the importance of a suitable solid support as well as the enzyme immobilisation method. Recently, there has been increased interest in using nano-scale material e.g. using nanoparticles as enzyme support material. This is largely due to their advantages such as large surface area to volume ratio as well as reduced mass transfer resistance. Electrospinning is a straight forward and cost effective method for producing nanofibres from any soluble polymer(s). The applications of electrospun nanofibres have been reported in clinical studies, biofuel production as well as bioremediation. In this study two polymers were selected: nylon for its mechanical stability and chitosan for its biocompatibility and hydrophilicity, for the fabrication of electrospun nanofibres which would function as immobilisation support material for acetylcholinesterase. The first objective of this study was to electrospin nanofibres from a nylon-6 and chitosan blend solution. A binary solvent system consisting of formic acid and acetic acid (50:50) successfully dissolved and blended the polymers which were subsequently electrospun. Scanning electron microscopy characterisation of the nanofibres showed that (i) a nylon-6: chitosan ratio of 16%: 3% resulted in the formation of bead free nanofibres and (ii) the fibres were collected in non-woven mats characterised by different size nanofibres with average diameters of 250 nm for the main fibres and 40 nm for the smaller nanofibres. Fourier transform infra-red (FT-IR) analysis of the nanofibres indicated that a new product had been formed during the blending of the two polymers. The second aim of the study was to carry out a facile immobilisation of electric eel acetylcholinesterase via glutaraldehyde (GA) cross-linking. Glutaraldehyde solution 5% (v/v) resulted in the immobilisation of 0.334 mg/cmÂ² of acetylcholinesterase onto the nanofibres. The immobilisation procedure was optimised with reference to acetylcholinestease and crosslinker concentrations, incubation time and the cross-linking method. A comparative investigation into the optimum pH and temperature conditions, pH and thermal stabilities, substrate and inhibition kinetics was then carried out on free and immobilised acetylcholinesterase. The final objective of this study was to determine the storage stabilities of the immobilised and free enzymes as well as the reusability characteristics of the immobilised acetylcholinesterase. Several conclusions were drawn from this study. Acetylcholinesterase was successfully immobilised onto the surface of nylon-6:chitosan nanofibres with retention of its activity. There was a shift in the pH optimum of the immobilised acetylcholineseterase by 0.5 units towards a neutral pH. Although both free and immobilised acetylcholinesterase exhibited the same optimum temperature, immobilised acetylcholinesterase showed enhanced thermal stability. In terms of pH stability, immobilised acetylcholinesterase showed greater stability at acidic pH whilst free acetylcholinesterase was more stable under alkaline pH conditions. Relative to free acetylcholinesterase, the immobilised enzyme showed considerable storage stability retaining ~50% of its activity when stored for 49 days at 4Â°C. Immobilised acetylcholinesterase also retained > 20% of its initial activity after 9 consecutive reuse cycles. When exposed to fixed concentrations of carbofuran or demeton-S-methyl sulfone, immobilised acetylcholinesterase showed similar inhibition characteristics to that of the free enzyme. The decrease in enzyme activity observed after immobilisation to the nanofibres may have been due to several reasons which include some enzyme molecules being immobilised in structural conformations which reduced substrate access to the catalytic site, participation of the catalytic residues in immobilisation and enzyme denaturation due to the reaction conditions used for acetylcholinesterase immobilisation. Similar observations have been widely reported in literature and this is one of the major drawbacks of enzyme immobilisation. In conclusion, nylon-6:chitosan electrospun nanofibres were shown to be suitable supports for facile acetylcholinesterase immobilisation and the immobilised enzyme has potential for use in pesticide detection. Future recommendations for this study include a comparative study of the GA cross-linking method for AChE immobilisation which will lead to more intensely bound enzyme molecules to prevent non-specific binding. An investigation into the effect of inhibitors on stored immobilised AChE, as well as reactivation and reuse studies, may also be useful for determining the cost-effectiveness of reusing immobilised AChE for pesticide detection in environmental water samples. Several models have been designed for the determination of the kinetic parameters for immobilised enzymes. These take into account the mass transfer resistance as well as the overall charge of the immobilisation matrix. The use of these models to analyse experimental data will give a clear understanding of the effects of immobilisation on enzyme activity
Keywords: Acetylcholinesterase; Acetylcholinesterase -- Inhibitors; Electric eel; Biosensors; Immobilized enzymes; Pesticides -- Environmental aspects; Pesticides -- Toxicology; Nylon; Chitosan; Nanofibers; Electrospinning